富含二十碳五烯酸(EPA)或二十二碳六烯酸(DHA)之飲食對老化促進小鼠(SAMP8)在強迫游水實驗模式下行為表現之影響 - 黃俊傑; Huang Jun-Jie (2010)
中文摘要.I 英文摘要.II 目 錄.III 圖目錄.VII 表目錄.VIII 第一章 緒論.1 第二章 文獻回顧.2 第一節 憂鬱症(Depression).2 第二節 抗憂鬱藥物與情緒及行為之影響.8 第三節 魚油與情緒及行為之表現.11 第四節 憂鬱症之動物行為研究模式.14 第五節 單胺類氧化酶.16 第六節 腦源性神經營養因子.18 第三章 研究動機與目的.20 第四章 實驗設計與方法.22 第一節 實驗流程.22 第二節 實驗動物與飼養環境.23 第三節 實驗飲食組成.24 第四節 樣本收集與處理.25 第五節 分析項目與方法.26 第六節 統計分析.40 第五章 結果.41 第一節 體重與腦部組織重量.41 第二節 強迫游水試驗.42 第三節 血漿脂肪酸組成之比較.44 第四節 紅血球脂肪酸組成之比較.46 第五節 腦部前額葉皮質區脂肪酸組成之比較.48 第六節 強迫游水試驗之行為表現與多元不飽和脂肪酸濃度之相…50 第七節 腦部前額葉皮質區單胺氧化酶活性.53 第八節 腦部前額葉皮質區腦源性神經營養因子濃度.54 第六章 討論.55 第一節 體重與腦部重量變化之比較.55 第二節 行為表現之探討.56 第三節 脂肪酸組成之探討.59 第四節 單胺類氧化酶-A對於行為表現之影響.65 第五節 腦源性神經營養因子對於行為表現之影響.66 第七章 結論.67 參考文獻.85 附錄一、動物實驗審查申請書.93 1. Kessler RC, Chiu WT, Demler O, Merikangas KR, Walters EE: Prevalence, severity, and comorbidity of 12-month DSM-IV disorders in the National Comorbidity Survey Replication. Arch Gen Psychiatry 2005, 62(6):617-627. 2. Murray CJ, Lopez AD: Alternative projections of mortality and disability by cause 1990-2020: Global Burden of Disease Study. Lancet 1997, 349(9064):1498-1504. 3. The global burden of disease. In.: World Health Organization; 2008. 4. Shen YC, Zhang MY, Huang YQ, He YL, Liu ZR, Cheng H, Tsang A, Lee S, Kessler RC: Twelve-month prevalence, severity, and unmet need for treatment of mental disorders in metropolitan China. Psychol Med 2006, 36(2):257-267. 5. Dennis CL: Psychosocial and psychological interventions for prevention of postnatal depression: systematic review. BMJ 2005, 331(7507):15. 6. Williams DR, Gonzalez HM, Neighbors H, Nesse R, Abelson JM, Sweetman J, Jackson JS: Prevalence and distribution of major depressive disorder in African Americans, Caribbean blacks, and non-Hispanic whites: results from the National Survey of American Life. Arch Gen Psychiatry 2007, 64(3):305-315. 7. Burden of mental and behavioral disorder. In.: World Health Organization; 2001. 8. International Association for Suicide Prevention In.: World Suicide Prevention Day; 2006. 9. Cognitive Difficulties Associated With Depression: What Are the Implications for Treatment? . In.: Psychiatric Times; 2009. 10. Consensus Guidelines : for Assessment and Management of Depression in the Elderly. In.: Faculty of Psychiatry of Old Age, NSW Branch, RANZCP; 2001. 11. Psychiatric Research Report 12. 廖以誠、葉宗烈、楊延光、盧豐華、張智仁、柯慧貞、駱重鳴: 台灣老年憂鬱量表之編製與信、效度研究. 台灣精神醫學 2004, 18:11. 13. Yesavage JA, Brink TL, Rose TL, Lum O, Huang V, Adey M, Leirer VO: Development and validation of a geriatric depression screening scale: a preliminary report. J Psychiatr Res 1982, 17(1):37-49. 14. Yeh TL LI, Yang YK, Ko HC, Chang CJ, Lu FH: Geriatric Depression Scale (Taiwanese and Mandarin Translations). Clinical Gerontologist 1995, 15:3. 15. Kato N: Neurophysiological mechanisms of electroconvulsive therapy for depression. Neurosci Res 2009, 64(1):3-11. 16. Scocco P, Toffol E: [Group interpersonal psychotherapy: a review]. Sante Ment Que 2008, 33(2):105-131. 17. Anderson IM, Tomenson BM: Treatment discontinuation with selective serotonin reuptake inhibitors compared with tricyclic antidepressants: a meta-analysis. BMJ 1995, 310(6992):1433-1438. 18. Lepola U, Arato M, Zhu Y, Austin C: Sertraline versus imipramine treatment of comorbid panic disorder and major depressive disorder. J Clin Psychiatry 2003, 64(6):654-662. 19. Krishnan V, Nestler EJ: The molecular neurobiology of depression. Nature 2008, 455(7215):894-902. 20. Kris-Etherton PM, Harris WS, Appel LJ: Fish consumption, fish oil, omega-3 fatty acids, and cardiovascular disease. Circulation 2002, 106(21):2747-2757. 21. SanGiovanni JP, Parra-Cabrera S, Colditz GA, Berkey CS, Dwyer JT: Meta-analysis of dietary essential fatty acids and long-chain polyunsaturated fatty acids as they relate to visual resolution acuity in healthy preterm infants. Pediatrics 2000, 105(6):1292-1298. 22. Morgan C, Davies L, Corcoran F, Stammers J, Colley J, Spencer SA, Hull D: Fatty acid balance studies in term infants fed formula milk containing long-chain polyunsaturated fatty acids. Acta Paediatr 1998, 87(2):136-142. 23. Young C, Hikita T, Kaneko S, Shimizu Y, Hanaka S, Abe T, Shimasaki H, Ikeda R, Miyazawa Y, Nakajima A: Fatty acid compositions of colostrum, cord blood, maternal blood and major infant formulas in Japan. Acta Paediatr Jpn 1997, 39(3):299-304. 24. Manerba A, Vizzardi E, Metra M, Dei Cas L: n-3 PUFAs and cardiovascular disease prevention. Future Cardiol 2010, 6(3):343-350. 25. Murakami K, Mizoue T, Sasaki S, Ohta M, Sato M, Matsushita Y, Mishima N: Dietary intake of folate, other B vitamins, and omega-3 polyunsaturated fatty acids in relation to depressive symptoms in Japanese adults. Nutrition 2008, 24(2):140-147. 26. Freeman MP: Omega-3 fatty acids and perinatal depression: a review of the literature and recommendations for future research. Prostaglandins Leukot Essent Fatty Acids 2006, 75(4-5):291-297. 27. Timonen M, Horrobin D, Jokelainen J, Laitinen J, Herva A, Rasanen P: Fish consumption and depression: the Northern Finland 1966 birth cohort study. J Affect Disord 2004, 82(3):447-452. 28. Hibbeln JR: Fish consumption and major depression. Lancet 1998, 351(9110):1213. 29. Bennett CN, Horrobin DF: Gene targets related to phospholipid and fatty acid metabolism in schizophrenia and other psychiatric disorders: an update. Prostaglandins Leukot Essent Fatty Acids 2000, 63(1-2):47-59. 30. Yehuda S, Rabinovitz S, Mostofsky DI: Essential fatty acids are mediators of brain biochemistry and cognitive functions. J Neurosci Res 1999, 56(6):565-570. 31. Chalon S: Omega-3 fatty acids and monoamine neurotransmission. Prostaglandins Leukot Essent Fatty Acids 2006, 75(4-5):259-269. 32. Xiao Y, Li X: Polyunsaturated fatty acids modify mouse hippocampal neuronal excitability during excitotoxic or convulsant stimulation. Brain Res 1999, 846(1):112-121. 33. Poling JS, Karanian JW, Salem N, Jr., Vicini S: Time- and voltage-dependent block of delayed rectifier potassium channels by docosahexaenoic acid. Mol Pharmacol 1995, 47(2):381-390. 34. Bjerve KS: Omega 3 fatty acid deficiency in man: implications for the requirement of alpha-linolenic acid and long-chain omega 3 fatty acids. World Rev Nutr Diet 1991, 66:133-142. 35. Seo T, Blaner WS, Deckelbaum RJ: Omega-3 fatty acids: molecular approaches to optimal biological outcomes. Curr Opin Lipidol 2005, 16(1):11-18. 36. Nemets H, Nemets B, Apter A, Bracha Z, Belmaker RH: Omega-3 treatment of childhood depression: a controlled, double-blind pilot study. Am J Psychiatry 2006, 163(6):1098-1100. 37. Peet M, Horrobin DF: A dose-ranging study of the effects of ethyl-eicosapentaenoate in patients with ongoing depression despite apparently adequate treatment with standard drugs. Arch Gen Psychiatry 2002, 59(10):913-919. 38. Butterfield DA, Howard BJ, Yatin S, Allen KL, Carney JM: Free radical oxidation of brain proteins in accelerated senescence and its modulation by N-tert-butyl-alpha-phenylnitrone. Proc Natl Acad Sci U S A 1997, 94(2):674-678. 39. Higuchi K, Matsumura A, Hashimoto K, Honma A, Takeshita S, Hosokawa M, Yasuhira K, Takeda T: Isolation and characterization of senile amyloid--related antigenic substance (SASSAM) from mouse serum. Apo SASSAM is a low molecular weight apoprotein of high density lipoprotein. J Exp Med 1983, 158(5):1600-1614. 40. Flood JF, Morley JE: Learning and memory in the SAMP8 mouse. Neurosci Biobehav Rev 1998, 22(1):1-20. 41. Porsolt RD, Anton G, Blavet N, Jalfre M: Behavioural despair in rats: a new model sensitive to antidepressant treatments. Eur J Pharmacol 1978, 47(4):379-391. 42. Porsolt RD, Le Pichon M, Jalfre M: Depression: a new animal model sensitive to antidepressant treatments. Nature 1977, 266(5604):730-732. 43. Fedorova I, Salem N, Jr.: Omega-3 fatty acids and rodent behavior. Prostaglandins Leukot Essent Fatty Acids 2006, 75(4-5):271-289. 44. Leahy-Warren P, McCarthy G: Postnatal depression: prevalence, mothers' perspectives, and treatments. Arch Psychiatr Nurs 2007, 21(2):91-100. 45. Shih JC, Chen K, Ridd MJ: Monoamine oxidase: from genes to behavior. Annu Rev Neurosci 1999, 22:197-217. 46. Pedersen NL, Oreland L, Reynolds C, McClearn GE: Importance of genetic effects for monoamine oxidase activity in thrombocytes in twins reared apart and twins reared together. Psychiatry Res 1993, 46(3):239-251. 47. Murphy DL, Brand E, Goldman T, Baker M, Wright C, van Kammen D, Gordon E: Platelet and plasma amine oxidase inhibition and urinary amine excretion changes during phenelzine treatment. J Nerv Ment Dis 1977, 164(2):129-134. 48. Stahl S, Briley M: Understanding pain in depression. Hum Psychopharmacol 2004, 19 Suppl 1:S9-S13. 49. Saura J, Luque JM, Cesura AM, Da Prada M, Chan-Palay V, Huber G, Loffler J, Richards JG: Increased monoamine oxidase B activity in plaque-associated astrocytes of Alzheimer brains revealed by quantitative enzyme radioautography. Neuroscience 1994, 62(1):15-30. 50. Vindis C, Seguelas MH, Bianchi P, Parini A, Cambon C: Monoamine oxidase B induces ERK-dependent cell mitogenesis by hydrogen peroxide generation. Biochem Biophys Res Commun 2000, 271(1):181-185. 51. Boulton AA, Eisenhofer G: Catecholamine metabolism. From molecular understanding to clinical diagnosis and treatment. Overview. Adv Pharmacol 1998, 42:273-292. 52. Thoenen H: Neurotrophins and neuronal plasticity. Science 1995, 270(5236):593-598. 53. Lindsay RM, Wiegand SJ, Altar CA, DiStefano PS: Neurotrophic factors: from molecule to man. Trends Neurosci 1994, 17(5):182-190. 54. Lindholm D, Carroll P, Tzimagiogis G, Thoenen H: Autocrine-paracrine regulation of hippocampal neuron survival by IGF-1 and the neurotrophins BDNF, NT-3 and NT-4. Eur J Neurosci 1996, 8(7):1452-1460. 55. Monteleone P, Serritella C, Martiadis V, Maj M: Decreased levels of serum brain-derived neurotrophic factor in both depressed and euthymic patients with unipolar depression and in euthymic patients with bipolar I and II disorders. Bipolar Disord 2008, 10(1):95-100. 56. Nibuya M, Morinobu S, Duman RS: Regulation of BDNF and trkB mRNA in rat brain by chronic electroconvulsive seizure and antidepressant drug treatments. J Neurosci 1995, 15(11):7539-7547. 57. Kuroda Y, McEwen BS: Effect of chronic restraint stress and tianeptine on growth factors, growth-associated protein-43 and microtubule-associated protein 2 mRNA expression in the rat hippocampus. Brain Res Mol Brain Res 1998, 59(1):35-39. 58. Conti AC, Cryan JF, Dalvi A, Lucki I, Blendy JA: cAMP response element-binding protein is essential for the upregulation of brain-derived neurotrophic factor transcription, but not the behavioral or endocrine responses to antidepressant drugs. J Neurosci 2002, 22(8):3262-3268. 59. Rios M, Fan G, Fekete C, Kelly J, Bates B, Kuehn R, Lechan RM, Jaenisch R: Conditional deletion of brain-derived neurotrophic factor in the postnatal brain leads to obesity and hyperactivity. Mol Endocrinol 2001, 15(10):1748-1757. 60. Folch J, Lees M, Sloane Stanley GH: A simple method for the isolation and purification of total lipides from animal tissues. J Biol Chem 1957, 226(1):497-509. 61. Siufi AA, Cotrim GDSID, De Cassia MDR, Takita LC, Rodrigues De Lima G, Goncalves WJ: Effects of tamoxifen therapy on the expression of p27 protein in the endometrium of women with primary breast cancer. Int J Oncol 2003, 23(6):1545-1551. 62. Smith PK, Krohn RI, Hermanson GT, Mallia AK, Gartner FH, Provenzano MD, Fujimoto EK, Goeke NM, Olson BJ, Klenk DC: Measurement of protein using bicinchoninic acid. Anal Biochem 1985, 150(1):76-85. 63. Lucki I: The forced swimming test as a model for core and component behavioral effects of antidepressant drugs. Behav Pharmacol 1997, 8(6-7):523-532. 64. Xu Q, Pan Y, Yi LT, Li YC, Mo SF, Jiang FX, Qiao CF, Xu HX, Lu XB, Kong LD et al: Antidepressant-like effects of psoralen isolated from the seeds of Psoralea corylifolia in the mouse forced swimming test. Biol Pharm Bull 2008, 31(6):1109-1114. 65. Levant B, Ozias MK, Davis PF, Winter M, Russell KL, Carlson SE, Reed GA, McCarson KE: Decreased brain docosahexaenoic acid content produces neurobiological effects associated with depression: Interactions with reproductive status in female rats. Psychoneuroendocrinology 2008, 33(9):1279-1292. 66. Lakhwani L, Tongia SK, Pal VS, Agrawal RP, Nyati P, Phadnis P: Omega-3 fatty acids have antidepressant activity in forced swimming test in Wistar rats. Acta Pol Pharm 2007, 64(3):271-276. 67. Lin PY, Su KP: A meta-analytic review of double-blind, placebo-controlled trials of antidepressant efficacy of omega-3 fatty acids. J Clin Psychiatry 2007, 68(7):1056-1061. 68. Bourre JM, Dumont O, Piciotti M, Clement M, Chaudiere J, Bonneil M, Nalbone G, Lafont H, Pascal G, Durand G: Essentiality of omega 3 fatty acids for brain structure and function. World Rev Nutr Diet 1991, 66:103-117. 69. Su KP: Mind-body interface: the role of n-3 fatty acids in psychoneuroimmunology, somatic presentation, and medical illness comorbidity of depression. Asia Pac J Clin Nutr 2008, 17 Suppl 1:151-157. 70. Stoll AL, Severus WE, Freeman MP, Rueter S, Zboyan HA, Diamond E, Cress KK, Marangell LB: Omega 3 fatty acids in bipolar disorder: a preliminary double-blind, placebo-controlled trial. Arch Gen Psychiatry 1999, 56(5):407-412. 71. Adams PB, Lawson S, Sanigorski A, Sinclair AJ: Arachidonic acid to eicosapentaenoic acid ratio in blood correlates positively with clinical symptoms of depression. Lipids 1996, 31 Suppl:S157-161. 72. Su KP, Huang SY, Peng CY, Lai HC, Huang CL, Chen YC, Aitchison KJ, Pariante CM: Phospholipase A2 and cyclooxygenase 2 genes influence the risk of interferon-alpha-induced depression by regulating polyunsaturated fatty acids levels. Biol Psychiatry 2010, 67(6):550-557. 73. Chang JP, Chen YT, Su KP: Omega-3 Polyunsaturated Fatty Acids (n-3 PUFAs) in Cardiovascular Diseases (CVDs) and Depression: The Missing Link? Cardiovasc Psychiatry Neurol 2009, 2009:725310. 74. Williams CM, Burdge G: Long-chain n-3 PUFA: plant v. marine sources. Proc Nutr Soc 2006, 65(1):42-50. 75. Konsman JP, Parnet P, Dantzer R: Cytokine-induced sickness behaviour: mechanisms and implications. Trends Neurosci 2002, 25(3):154-159. 76. Uehara A, Ishikawa Y, Okumura T, Okamura K, Sekiya C, Takasugi Y, Namiki M: Indomethacin blocks the anorexic action of interleukin-1. Eur J Pharmacol 1989, 170(3):257-260. 77. Milton AS: Thermoregulatory actions of eicosanoids in the central nervous system with particular regard to the pathogenesis of fever. Ann N Y Acad Sci 1989, 559:392-410. 78. Lands WE: Biochemistry and physiology of n-3 fatty acids. FASEB J 1992, 6(8):2530-2536. 79. Song C, Phillips AG, Leonard BE, Horrobin DF: Ethyl-eicosapentaenoic acid ingestion prevents corticosterone-mediated memory impairment induced by central administration of interleukin-1beta in rats. Mol Psychiatry 2004, 9(6):630-638. 80. James MJ, Gibson RA, Cleland LG: Dietary polyunsaturated fatty acids and inflammatory mediator production. Am J Clin Nutr 2000, 71(1 Suppl):343S-348S. 81. Owen C, Rees AM, Parker G: The role of fatty acids in the development and treatment of mood disorders. Curr Opin Psychiatry 2008, 21(1):19-24. 82. Nakamura MT, Nara TY: Essential fatty acid synthesis and its regulation in mammals. Prostaglandins Leukot Essent Fatty Acids 2003, 68(2):145-150. 83. Lee HJ, Rao JS, Chang L, Rapoport SI, Kim HW: Chronic imipramine but not bupropion increases arachidonic acid signaling in rat brain: is this related to 'switching' in bipolar disorder? Mol Psychiatry 2010, 15(6):602-614. 84. Su KP, Huang SY, Chiu CC, Shen WW: Omega-3 fatty acids in major depressive disorder. A preliminary double-blind, placebo-controlled trial. Eur Neuropsychopharmacol 2003, 13(4):267-271. 85. Horrobin DF, Bennett CN: Depression and bipolar disorder: relationships to impaired fatty acid and phospholipid metabolism and to diabetes, cardiovascular disease, immunological abnormalities, cancer, ageing and osteoporosis. Possible candidate genes. Prostaglandins Leukot Essent Fatty Acids 1999, 60(4):217-234. 86. Chang CY, Ke DS, Chen JY: Essential fatty acids and human brain. Acta Neurol Taiwan 2009, 18(4):231-241. 87. Whalley LJ, Fox HC, Wahle KW, Starr JM, Deary IJ: Cognitive aging, childhood intelligence, and the use of food supplements: possible involvement of n-3 fatty acids. Am J Clin Nutr 2004, 80(6):1650-1657. 88. Aiguo W, Zhe Y, Gomez-Pinilla F: Vitamin E protects against oxidative damage and learning disability after mild traumatic brain injury in rats. Neurorehabil Neural Repair 2010, 24(3):290-298. 89. Ikeda K, Kurokawa M, Aoyama S, Kuwana Y: Neuroprotection by adenosine A2A receptor blockade in experimental models of Parkinson's disease. J Neurochem 2002, 80(2):262-270. 90. Shirayama Y, Chen AC, Nakagawa S, Russell DS, Duman RS: Brain-derived neurotrophic factor produces antidepressant effects in behavioral models of depression. J Neurosci 2002, 22(8):3251-3261. 根據世界衛生組織(World Health Organization, WHO)的流行病學調查指出，憂鬱症在2030年將成為世界第一的高負擔疾病，而年齡大於65歲的老年人比青壯年族群更易罹患憂鬱症。研究指出造成老年人憂鬱症的原因可能為神經退化所導致，進而影響了神經訊息傳導物質濃度降低與認知功能喪失等。本實驗將探討富含二十碳五烯酸(eicosapentaenoic acid；EPA)及二十二碳六烯酸(docosahexaenoic；DHA)之飲食對於雄性老化促進小鼠Senescence accelerated-prone 8 (SAMP8)行為表現之影響。實驗期間分別給予五月齡大54隻SAMP8小鼠富含大豆油(基礎組、控制組及正控制組-投予抑鬱劑imipramine)、富含EPA之魚油(EPA>60%)及DHA之魚油(DHA>50%)的飲食，共計五組。各組實驗組經十二週的飲食介入後進行強迫游水試驗(forced swimming test, FST )分析並犧牲，分析其血漿、紅血球及腦部前額葉皮質之脂肪酸組成，並分析腦部前額葉皮質之單胺氧化酶-A和-B (monoamine oxidase A & B, MAO-A & MAO-B)活性及腦衍生神經滋養因子(brain derived neurotrophic factor, BDNF)濃度。於強迫游水試驗中發現，EPA組及DHA組其靜止時間顯著低於控制組(p<0.05)，而腦衍生神經滋養因子濃度與控制組相比顯著提高(p<0.05)；此兩者結果呈現顯著負相關，推測EPA及DHA可能因BDNF的濃度而間接改善FST所引發之類似憂鬱情境。EPA及DHA組之MAO-A活性顯著低於控制組(p<0.05)，而EPA組之MAO-B活性顯著低於控制組(p<0.05)，推測可能藉由降低MAO-A&B的活性而減少神經傳導物質的代謝，進而改善憂鬱情境。因此本次研究結果發現，富含EPA及DHA之飲食可能改善老化促進小鼠於壓力環境下類似憂鬱情境之行為表現，同時發現EPA改善的效果高於DHA。 The recent epidemiological data of World Health Organization (WHO) pointed out that unipolar depressive disorder will become one of the high burdens of disease in 2030. The age over 65-year-old elderly is more likely to suffer depression than young ethnic groups. Recent reports show that elderly depression may result in the aging of neural degeneration, decrease the level of neurotransmitters and transmission of nerve signals and/or disability cognitive function eventually. In this study, we aimed to assess the eicosapentaenoic acid- (EPA-) and docosahexaenoic acid-rich (DHA-rich) diets protective effect on behavior test in aging male senescence accelerated-prone 8 (SAMP8) mice. Fifty-four 5-month-old aged SAMP8 mice were housed and fed with the various diets, which including soybean-oil-riched diet groups (base group, control group and the positive control group, imipramine-injected group), EPA-riched and (EPA>60%) and DHA-riched (DHA>50%) diet groups. After 12-week dietary intervention, animals were evaluated by behavior tset (under forced swimming test; FST), sacrificed and blood and selected organ for further biochemical analyses. The fatty acid profiles of plasma, erythrocyte and brain prefrontal cortex were analyzed. The monoamine oxidase A & B (MAO-A & MAO-B) activity and the level of brain derived neurotrophic factor (BDNF) concentration in brain were also examined. Results of the force swimming test showed that EPA- and DHA-rich groups showed significant shorter immobile time than the control group (p<0.05) and EPA-rich group showed significant higher BDNF level than control group (p<0.05). Both results showed highly significant negative correlation, it is reasonably to presume the anti-depressive effect of EPA and DHA may depend on the level of BDNF and EPA, DHA may indirectly improve depression-like behavior under FST. The decreasing MAO-A activity was observed in EPA and DHA group, and the EPA group of MAO-B activity significantly lower than the control group (p<0.05). It’s possible by reducing MAO-A & MAO-B activity and resulted to restore neurotransmitters metabolism, which may direct and/or indirect improve the depression-like behavior. In conclusion, this study found that EPA- and DHA-riched dietary may improve the SAMP8 mice under pressure which presents the antidepressant-like behavior ability, specifically in EPA-riched diet.